The Role of Left Tail Risk in Explaining the Idiosyncratic Volatility Puzzle - Mahshid Shahrzadi; Darioush Foroughi (مطالعات تجربی حسابداری مالی, 2022)
The Aim of this study is to introduce the left tail risk as a driver for creating idiosyncratic volatility and explainer the negative returns due to high unsystematic volatility. In addition, the present study is trying to determine how the idiosyncratic volatility puzzle occurs. In this study, univariate and bivariate portfolio analysis as well as Fama and Macbeth (1973) regression have been used. For this purpose, the information of Tehran stock exchange and Iran fara bourse companies during the years 1384 to 1398 has been used. The results of this study indicate the existence of the idiosyncratic volatility puzzle (the low (high) returns of high (low) idiosyncratic volatility stocks) and left tail risk anomaly (the low (high) returns of high (low) left tail risk) in the research sample. The idiosyncratic volatility puzzle (the low (high) returns of high (low) idiosyncratic volatility stocks) is no longer detected when idiosyncratic volatility-sorted portfolios are neutralized to left tail risk, regression control for left tail risk and factor models include a left tail risk factor. The left tail risk plays the important role to explain idiosyncratic volatility puzzle (the low returns of high idiosyncratic volatility stocks) and the reason for this explanation is the falling stock price pressure with high left-tail risk on stocks with high unsystematic volatility.